2012
DOI: 10.1111/j.1440-1746.2011.07006.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti‐fibrotic modalities for liver fibrosis: Molecular targeting and regenerative medicine in fibrosis therapy

Abstract: Based on the cellular and molecular mechanisms underlying hepatic fibrogenesis, several kinds of approaches have been proposed to treat liver fibrosis. Among a number of growth factors and cytokines that regulate collagen metabolism, transforming growth factor (TGF)-β is the most potent factor to accelerate liver fibrosis by activating hepatic stellate cells, stimulating collagen gene transcription, and suppressing matrix metalloproteinases expression. Thus, TGF-β as well as its intracellular mediators, Smad p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…5A). Smad3 phosphorylation is an important determinant of its nuclear translocation [38]. Consistent with the reduction in phosphorylated Smad3 by ASTX, the nuclear translocation of Smad3 was also reduced by ASTX, whereas TGFβ1 treatment increased nuclear Smad3 levels (Fig.…”
Section: Astx Attenuated Phosphorylation and Nuclear Translocation Ofsupporting
confidence: 73%
“…5A). Smad3 phosphorylation is an important determinant of its nuclear translocation [38]. Consistent with the reduction in phosphorylated Smad3 by ASTX, the nuclear translocation of Smad3 was also reduced by ASTX, whereas TGFβ1 treatment increased nuclear Smad3 levels (Fig.…”
Section: Astx Attenuated Phosphorylation and Nuclear Translocation Ofsupporting
confidence: 73%
“…Based on extensive in vitro and animal data, TGF-β has long been suspected as an important mediator of fibrosis in SSc as well as a variety of other fibrotic diseases, including renal, pulmonary, cardiac, and liver fibrosis (29)(30)(31). However, to our knowledge there has never previously been clinical data directly supporting its role in humans.…”
Section: Discussionmentioning
confidence: 85%
“…Another strategy using the traditional Chinese medicine Haobie Yangyin Ruanjian decoction (HYRD) inhibited liver fibrosis induced by CCl4 in rats, likely through downregulation of the TGF-β/Smad fibrogenic signaling pathway (Yang et al 2010). Another study indicated that Y-box protein-1 (YB-1) is a negative regulator of collagen expression by physically interacting with p300/ Smad3, thereby abrogating the stimulatory effect of TGF-β and liver fibrosis induced by CCl4 in mice (Inagaki et al 2012). The novel small compound HSc025 can bind to the C-terminal region of YB-1 and promote the nuclear import of YB-1, resulted in the suppression of collagen gene expression (Higashi et al 2011).…”
Section: Management Of Other Immune Cells: Previous Reportsmentioning
confidence: 97%
“…TGF-β induces the phosphorylation of Smad3 and reduces formation of the Smad3/4 complex, thereby inducing Smad DNA-binding activity to stimulate the expression of collagen and suppress MMP expression (Inagaki et al 2012). Therefore, nuclear accumulation of phosphorylated Smad3 is the most common feature observed in activated HSCs, and the inhibition of Smad3 accumulation or export to nuclear can suppress the transcriptional activity of the collagen gene (Inagaki et al 2012).…”
Section: Inflammatory Response After Liver Injurymentioning
confidence: 97%